(untitled) (Business Vision, 2020)
The article is part of the research project entitled: “Dynamics of agricultural sector exports and its impact on sustainable rural development in the department of Nariño in the period 2010-2018”, research that seeks to contribute with mechanisms that allow strengthening and encourage agricultural and agro-industrial exports from Nariño based on trends in international demand and sustainable development. The characterization of the exportable supply of the agricultural and agro-industrial sector in the period between 2010 and 2018, allows to identify and make visible the contribution of exporting companies, as well as the specific identification of the productive and competitive capacities of the Department of Nariño. The Department of Nariño in the 2018 period, exported products from the agricultural sector to the Republic of Ecuador for a FOB value of US 5.971.556 in 2018, the destination cities of agricultural products of Nariño origin are: Tulcán in 74% ; Emeraldas with 21%, Tachina with 3%. The Department of Nariño for 2018 exported 5.963.626 net kilos of fresh or dried oranges to the city of Tulcán, 477.053 net kilos of Tahiti Lima (Tahiti len) (citrus latifolia), fresh or dried, and 913.150 net kilos, of Crude palm oil to the city of Esmeralda and Táchira in the Republic of Ecuador through the Rumichaca international bridge border crossing, the transport used for each case is land transport.